1999
DOI: 10.1016/s0550-3213(99)00490-3
|View full text |Cite
|
Sign up to set email alerts
|

Properties of semi-chiral superfields

Abstract: Whenever the N = (2, 2) supersymmetry algebra of non-linear σ-models in two dimensions does not close off-shell, a holomorphic two-form can be defined. The only known superfields providing candidate auxiliary fields to achieve an off-shell formulation are semi-chiral fields. Such a semi-chiral description is only possible when the two-form is constant. Using an explicit example, hyperKähler manifolds, we show that this is not always the case. Finally, we give a concrete construction of semi-chiral potentials f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 21 publications
3
84
0
Order By: Relevance
“…As shown in the appendix, this implies that the real component (super)fields depicted by the nodes of the Adinkra may be complexified simultaneously with the two real components of D α+ . The appendix also proves that the supermultiplet depicted by (3.7) is one of the two semi-chiral supermultiplets [31,33], the other one obtained by swapping the assignment to the edges D α+ ↔ D . …”
Section: Adinkra Bmentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in the appendix, this implies that the real component (super)fields depicted by the nodes of the Adinkra may be complexified simultaneously with the two real components of D α+ . The appendix also proves that the supermultiplet depicted by (3.7) is one of the two semi-chiral supermultiplets [31,33], the other one obtained by swapping the assignment to the edges D α+ ↔ D . …”
Section: Adinkra Bmentioning
confidence: 81%
“…Worldsheet dimensional extension is thus a stepping stone towards dimensional extension to higher-dimensional spacetimes. Of course, worldsheet supersymmetry is also important in its own right [23][24][25][26] and affords comparison with numerous known results; see [2,5,[27][28][29][30][31][32][33][34][35], to name but a few.…”
Section: Introduction Results and Summarymentioning
confidence: 99%
“…and find the metric and B-field using this matrix as follows [14] (cf. 4.24) We assume that in a neighborhood of x 0 , the ranks of π ± are constant, and as result, the rank of σ is constant.…”
Section: The Structure Of Coker[j + J − ]mentioning
confidence: 99%
“…In a classic paper, Gates, Hull and Roček [3] showed that, for a 2-dimensional sigma model, the most general target space geometry allowing for (2, 2) supersymmetry was biHermitian or Kaehler with torsion geometry. This is characterized by a Riemannian metric g ab , two generally non commuting complex structures K ± a b and a closed 3-form H abc , such that g ab is Hermitian with respect to both the K ± a b and the K ± a b are parallel with respect to two different metric connections with torsion proportional to ±H abc [4][5][6][7]. This geometry is more general than that considered by Witten, which corresponds to the case where K + a b = ±K − a b and H abc = 0.…”
Section: Introductionmentioning
confidence: 99%